"I have only checked after the event": consumer approaches to safe online shopping - Whittaker, Jack Mark (Scams, cons, frauds, and deceptions, 2024)
Online shopping has now become very common, with consumers increasingly opting to purchase products on the World Wide Web instead of visiting traditional “bricks and mortar” stores, particularly during the COVID-19 pandemic. This has, however, also provided significant opportunities for offenders to abuse the inherent trust-based nature of online shopping, whereby consumers typically do not see the products physically prior to purchasing them. As such, this article sets out to examine the actions and behaviors that individuals take to prevent online shopping fraud and what, if any, discrepancy exists between prevention messaging and consumer behavior. To accomplish this, the study utilizes secondary survey data (n = 3478 respondents) obtained from a private-sector initiative called ScamAdviser. The results find that many respondents do not use appropriate behaviors to reduce their risk when shopping online and that furthermore there is reason to believe that consumers are not served well by the online safety advice that they are given. The paper argues that there is scope to increase guardianship through better prevention advice being communicated to online shoppers.